Cutaneous Mucormycosis in a Patient With Cirrhosis: A Case Report - Haley Belt MD; Margaret Kypreos MD; An Lu MD; Ginna Hernandez-Velasquez MD; Roma Mehta MD (Journal of Investigative Medicine High Impact Case Reports)
The global incidence of invasive mucormycosis (mucor) infection is on the rise due in part to an increased utilization of immunosuppressive therapies to treat malignancies and autoimmune diseases. While cirrhosis has previously been considered a risk factor for fungal infections, very little is known about the inciting factors precipitating development of isolated cutaneous mucormycosis infection. This form of mucor poses a significant mortality risk despite antifungal and surgical treatments and has been documented in only 5 patients with cirrhosis prior to our case report. This case report presents the sixth documented case of cutaneous mucormycosis in a patient with cirrhosis and explore nosocomial etiologies for its progression to clinically significant infection.